Copper foil, electrodes containing the same, and secondary batteries
Patent Information
- Application Number
- KR1020250057670
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-04-30
Smart Images

Figure 112025049533139-PAT00006_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a copper foil, an electrode containing the same, and a secondary battery. Background Technology
[0003] Rechargeable batteries are widely used as energy storage devices in various portable devices, electric vehicles, and energy storage systems (ESS). In particular, as high energy density and high power characteristics are simultaneously required, advanced technological development regarding electrode structures and constituent materials is continuously underway.
[0004] Generally, the cathode is formed by applying a slurry composed of an active material, a binder, and a conductive material to a current collector, followed by drying and roll pressing processes. Copper foil, which has excellent electrical conductivity and is easy to process, is widely used as the current collector.
[0005] Recently, as the demand for higher density and thinner electrodes has increased, design conditions such as increased active material coating, improved electrode density, and reduced electrode thickness are becoming increasingly sophisticated. Consequently, various performance requirements, including mechanical durability, process adaptability, surface precision, and coating uniformity, are being simultaneously imposed on copper foils.
[0006] In particular, when manufacturing electrodes, copper foil is repeatedly subjected to high-pressure roll presses and compressive loads of active materials, which can lead to various process problems such as reduced mechanical stability, wrinkling, tearing, softening, and surface defects.
[0007] Therefore, as electrode manufacturing conditions become more advanced, research is actively being conducted to optimize multifaceted characteristics such as copper foil thickness, crystal structure, surface roughness, chemical stability, and residual stress. The problem to be solved
[0009] The present invention provides a copper foil with improved mechanical properties and battery characteristics by improving the stability of the welded portion between the copper foil and the lead tab, an electrode including the same, and a secondary battery. means of solving the problem
[0011] The copper foil according to the present invention comprises a copper film doped with at least one element selected from nitrogen and sulfur, and has a welding strength of 50 kgf / mm² according to the following measurement method 1. 2 Up to 80 kgf / mm 2 It could be.
[0012] [Measurement Method 1]
[0013] 1) Prepare a copper film laminate in which 30 of the above copper films are stacked.
[0014] 2) The copper film laminate and the lead tab are welded according to the following laser welding conditions.
[0015] - Output: 2,500 W
[0016] - Impedance length: 39 mm
[0017] - Exposure interval: 1 mm
[0018] - Investigation time: 4 ms
[0019] 3) For the welded portion of the copper film laminate and the lead tab, the weld strength is measured using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min.
[0020] In one embodiment of the present invention, the welding strength according to the following measurement method 2 is 75 kgf / mm 2 Up to 100 kgf / mm 2 It could be.
[0021] [Measurement Method 2]
[0022] 1) Prepare a copper film laminate in which 50 of the above copper films are stacked.
[0023] 2) Measure the welding strength according to 2) and 3) of the above measurement method 1.
[0024] In one embodiment of the present invention, the total content of the doping element may be 20 ppm to 80 ppm.
[0025] In one embodiment of the present invention, the copper foil has a difference of 6 kgf / mm² between the first tensile strength at room temperature according to IPC-TM-650 and the second tensile strength after heat treatment at 190°C for 10 minutes. 2 The above is as follows, and the first tensile strength is 40 kgf / mm 2 Up to 70 kgf / mm 2 It could be.
[0026] In one embodiment of the present invention, the first welding efficiency according to Formula 1 below may be 100% to 140%.
[0027] [Equation 1]
[0028] First welding efficiency = (the above welding strength / the above first tensile strength) × 100
[0029] In one embodiment of the present invention, the second welding efficiency according to Formula 2 below may be 110% to 160%.
[0030] [Equation 2]
[0031] Second welding efficiency = (Above welding strength / Above second tensile strength) × 100
[0032] In one embodiment of the present invention, at a thickness of 6 μm ± 4 μm of the copper foil, the first elongation at room temperature according to the IPC-TM-650 may be 2% to 15%, and the second elongation after heat treatment at 190 ℃ for 10 minutes may be 3% to 20%.
[0033] In one embodiment of the present invention, the welding index based on the first elongation rate according to Formula 3 below may be 7 to 20.
[0034] [Equation 3]
[0035] First elongation-based welding index (unit omitted) = (Welding strength / First elongation)
[0036] In one embodiment of the present invention, the welding index based on the second elongation rate according to Formula 4 below may be 6 to 18.
[0037] [Equation 4]
[0038] Second elongation-based welding index (unit omitted) = (Welding strength above / Second elongation above)
[0039] In one embodiment of the present invention, the copper foil comprises a protective film formed on at least one surface of the copper film, and the protective film may comprise at least one of a chromium compound, a silane compound, and a nitrogen compound.
[0040] An electrode according to the present invention comprises a current collector including a copper foil and an active material layer formed on at least one surface of the current collector, wherein the copper foil comprises a copper film doped with at least one element selected from nitrogen and sulfur, and the welding strength according to the following measurement method 1 is 50 kgf / mm 2 Up to 90 kgf / mm 2 It could be.
[0041] [Measurement Method 1]
[0042] 1) Prepare a copper film laminate in which 30 of the above copper films are stacked.
[0043] 2) The copper film laminate and the lead tab are welded according to the following laser welding conditions.
[0044] - Output: 2,500 W
[0045] - Impedance length: 39 mm
[0046] - Exposure interval: 1 mm
[0047] - Investigation time: 4 ms
[0048] 3) For the welded portion of the copper film laminate and the lead tab, the weld strength is measured using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min.
[0049] A secondary battery according to the present invention comprises a negative electrode, a positive electrode, an electrolyte, and a separator interposed between the negative electrode and the positive electrode, wherein the negative electrode comprises a current collector comprising a copper foil, and the copper foil comprises a copper film doped with at least one element selected from nitrogen and sulfur, and the welding strength according to the following measurement method 1 is 50 kgf / mm 2 Up to 90 kgf / mm 2 It could be.
[0050] [Measurement Method 1]
[0051] 1) Prepare a copper film laminate in which 30 of the above copper films are stacked.
[0052] 2) The copper film laminate and the lead tab are welded according to the following laser welding conditions.
[0053] - Output: 2,500 W
[0054] - Impedance length: 39 mm
[0055] - Exposure interval: 1 mm
[0056] - Investigation time: 4 ms
[0057] 3) For the welded portion of the copper film laminate and the lead tab, the weld strength is measured using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min. Effects of the invention
[0059] The copper foil according to the present invention comprises a copper film doped with at least one element selected from nitrogen and sulfur, and the welding strength between the copper film laminate and the lead tab satisfies the range of 50 kgf / mm² to 80 kgf / mm². As a result, the mechanical properties of the copper foil are stably maintained at room temperature and high temperature, and local stress concentration in the weld is relieved, thereby suppressing the occurrence of defects such as cracks, delamination, or pores in the weld cross-section. In addition, the copper crystal can be stabilized and electron transport characteristics can be improved by doping with nitrogen and / or sulfur elements, so that the welding resistance is not excessively increased and stable electrical connection quality can be ensured. As a result, the bonding reliability and durability of the weld can be improved, and the structural stability of the electrode terminal can be maintained even under repeated charge and discharge conditions. Brief explanation of the drawing
[0061] Figure 1 schematically shows a cross-sectional view of a copper foil according to an embodiment. Figure 2 schematically shows a cross-sectional view of a cathode according to an embodiment. Figure 3 schematically shows a cross-sectional view of a secondary battery according to an embodiment. Figure 4 schematically shows a copper foil manufacturing apparatus according to an embodiment. Specific details for implementing the invention
[0062] The structural or functional descriptions of the embodiments disclosed in this specification or application are merely illustrative for the purpose of explaining embodiments according to the technical concept of the present invention. Embodiments according to the technical concept of the present invention may be implemented in various forms other than those disclosed in this specification or application, and the technical concept of the present invention is not to be interpreted as being limited to the embodiments described in this specification or application.
[0063] Furthermore, when a component is referred to as "comprising" in this specification or application, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components. Additionally, all numerical ranges indicating physical properties, dimensions, etc., of components described in this specification or application should be understood to be modified by the term "approximately" in all cases unless specifically stated otherwise. Furthermore, "ppm" in this specification or application refers to a weight basis. Moreover, "origin" in this specification or application refers to a component, structure, or the substance itself derived from a certain substance.
[0064] Additionally, terms such as "below" or "beneath," "lower," "above," and "upper" may be used in this specification or application to facilitate the description of the relationship between one element or component and another element or component as illustrated in the drawings. Spatially relative terms should be understood as terms that include different directions of the element during use or operation in addition to the directions illustrated in the drawings. For example, if the element illustrated in the drawings is flipped, the element described as "below" or "beneath" of another element may be placed "above" of the other element. Accordingly, the exemplary term "below" may include both the lower and upper directions. Likewise, the exemplary terms "above" or "upper" may include both the upper and lower directions.
[0066] The copper foil according to the present invention, the electrode including the same, and the secondary battery are described below.
[0068] Figure 1 schematically shows a cross-sectional view of a copper foil according to an embodiment.
[0069] The copper foil (10) according to the present invention may include a copper film (11). The copper film (11) may include copper (Cu) in an amount of 99 weight % or more, 99.3 weight % or more, 99.6 weight % or more, or 99.9 weight % or more.
[0070] The copper film (11) can be formed on a rotating cathode drum through electroplating. The copper film (11) may have a shiny surface that is in direct contact with the rotating cathode drum during the electroplating process and a matte surface on the opposite side. Specifically, the copper film (11) can be formed by the copper foil manufacturing device of FIG. 4 described later.
[0071] The copper film (11) may include a copper film doped with at least one element among nitrogen and sulfur. The doping element may affect the grain growth and stress distribution of the copper film (11), thereby simultaneously improving mechanical properties and interfacial stability.
[0072] Specifically, the nitrogen element can exist in the form of a coordination bond on the surface of copper, thereby improving the refinement of copper crystal grains and the strength of the particles. As a result, the tensile strength and elongation of the copper foil (10) can be secured in a balanced manner.
[0073] The above sulfur element can act as an activator for copper crystal grains, thereby improving the local deformation resistance of the copper film (11) and suppressing surface damage caused by heat concentration during the welding process with the lead tab. As a result, the possibility of cross-sectional defects occurring during welding of the copper film laminate and the lead tab is suppressed, and a stable intermetallic bonding state can be maintained without an increase in welding resistance.
[0074] The total content of the above doping element may be 20 ppm to 80 ppm, 25 ppm to 80 ppm, 25 ppm to 77 ppm, or 25 ppm to 75 ppm. When the above range is satisfied, the occurrence of bonding and increase in welding resistance at the welded cross-section of the copper foil (10) can be suppressed, and the welding strength can be improved.
[0075] The above doping element may be derived from a component included in the electrolyte during the copper film (11) manufacturing process described later. The above doping element can be identified by ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry). Alternatively, the above doping element can be identified by ToF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry).
[0076] The copper foil (10) may include a protective film (12) formed on at least one surface of the copper film (11). Although the protective film (12) formed on one surface of the copper film (11) is shown in FIG. 1, the protective film (12) may be formed on both surfaces of the copper film (11).
[0077] The protective film (12) may include at least one of a chromium compound, a silane compound, and a nitrogen compound. The protective film (12) can prevent oxidation and corrosion of the copper film (11) and improve heat resistance, thereby extending the lifespan of the copper foil (10) and the lifespan of the product containing the copper foil (10).
[0078] The copper foil (10) has a welding strength of 50 kgf / mm according to measurement method 1. 2 Up to 80 kgf / mm 2 It could be.
[0079] [Measurement Method 1]
[0080] 1) Prepare a copper film laminate in which 30 of the above copper films are stacked.
[0081] 2) The copper film laminate and the lead tab are welded according to the following laser welding conditions.
[0082] - Output: 2,500 W
[0083] - Impedance length: 39 mm
[0084] - Exposure interval: 1 mm
[0085] - Investigation time: 4 ms
[0086] 3) For the welded portion of the copper film laminate and the lead tab, the weld strength is measured using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min.
[0087] The welding strength may be an indicator of interfacial bonding reliability between the copper film laminate and the lead tab. The welding strength may be an indicator of durability against mechanical shock in the electrode containing the copper foil (10). The welding strength may be an indicator of interfacial bonding stability against mechanical stress that may occur during the manufacturing process of the secondary battery. The welding strength may be an indicator of structural stability and suppression of the increase in interfacial electrical resistance due to repeated charging and discharging of the secondary battery.
[0088] The welding strength can be adjusted according to whether the copper film (11) contains doping elements, the content of the doping elements, or the composition of the electrolyte and the content of each composition in the copper foil manufacturing process described later, and the manufacturing process conditions.
[0089] The welding strength according to the above measurement method 1 is 50 kgf / mm 2 Up to 80 kgf / mm 2 , 55 kgf / mm 2 Up to 80 kgf / mm 2 , 55 kgf / mm 2 Up to 75 kgf / mm 2 , or 55 kgf / mm2 Up to 70 kgf / mm 2 It could be.
[0090] In addition, the copper foil (10) has a welding strength of 75 kgf / mm according to the following measurement method 2. 2 Up to 100 kgf / mm 2 , 77 kgf / mm 2 Up to 100 kgf / mm 2 , 80 kgf / mm 2 Up to 100 kgf / mm 2 , or 80 kgf / mm 2 Up to 95 kgf / mm 2 It could be.
[0091] [Measurement Method 2]
[0092] 1) Prepare a copper film laminate in which 50 of the above copper films are stacked.
[0093] 2) Measure the welding strength according to 2) and 3) of the above measurement method 1.
[0094] If the above range is satisfied, the bonding reliability and durability of the weld between the copper film laminate and the lead tab can be improved, and the structural stability of the electrode terminal can be maintained even under repeated charge and discharge conditions.
[0095] The copper foil (10) has a difference of 6 kgf / mm between the first tensile strength at room temperature according to the IPC-TM-650 and the second tensile strength after heat treatment at 190°C for 10 minutes. 2 The above is as follows, and the first tensile strength is 40 kgf / mm 2 Up to 70 kgf / mm 2 It could be.
[0096] The copper foil (10) has a difference of 4 kgf / mm between the first tensile strength at room temperature according to the IPC-TM-650 and the second tensile strength after heat treatment at 190°C for 10 minutes. 2 The above is as follows, and the first tensile strength is 50 kgf / mm 2 Up to 70 kgf / mm 2It could be.
[0097] The copper foil (10) has a difference of 2 kgf / mm between the first tensile strength at room temperature according to the IPC-TM-650 and the second tensile strength after heat treatment at 190°C for 10 minutes. 2 The above is as follows, and the first tensile strength is 50 kgf / mm 2 Up to 65 kgf / mm 2 It could be.
[0098] When the above range is satisfied, the copper foil (10) can maintain a tensile strength of 85% or more relative to room temperature even after heat treatment, thereby suppressing peeling, bending, or fracture phenomena that may occur during the manufacturing process. In addition, the precision of electrode lamination can be improved, and long-term stability of the electrode structure can be secured.
[0099] The copper foil (10) above may have a first welding efficiency of 100% to 140% according to the following formula 1.
[0100] [Equation 1]
[0101] First welding efficiency = (the above welding strength / the above first tensile strength) × 100
[0102] The copper foil (10) above may have a second welding efficiency of 110% to 160% according to the following formula 2.
[0103] [Equation 2]
[0104] Second welding efficiency = (Above welding strength / Above second tensile strength) × 100
[0105] The first welding efficiency may be an indicator of the interfacial bonding quality and mechanical reliability of the copper foil (10) with the lead tab at room temperature. The second welding efficiency may be an indicator of the interfacial bonding stability and heat resistance reliability of the weldment of the copper foil (10) with the lead tab under a high-temperature environment.
[0106] The above first welding efficiency may be 100% to 140%, 105% to 140%, 105% to 138%, or 105% to 135%.
[0107] The above second welding efficiency may be 110% to 160%, 110% to 155%, 110% to 152%, or 110% to 150%.
[0108] When the above range is satisfied, the welded portion of the copper foil (10) with the lead tab can be stably maintained in room temperature and high temperature environments, thereby ensuring mechanical stability of the electrode structure including the copper foil (10).
[0109] At a thickness of 6 μm ± 4 μm of the copper foil (10), the first elongation rate at room temperature according to the IPC-TM-650 may be 2% to 15%, and the second elongation rate after heat treatment at 190 ℃ for 10 minutes may be 3% to 20%.
[0110] At a thickness of 6 μm ± 4 μm of the copper foil (10), the first elongation rate at room temperature according to the IPC-TM-650 may be 3% to 15%, and the second elongation rate after heat treatment at 190 ℃ for 10 minutes may be 4% to 20%.
[0111] At a thickness of 6 μm ± 4 μm of the copper foil (10), the first elongation rate at room temperature according to the IPC-TM-650 may be 3% to 12%, and the second elongation rate after heat treatment at 190 ℃ for 10 minutes may be 4% to 18%.
[0112] When the above range is satisfied, cracking or fracture of the copper foil (10) can be suppressed even under room temperature conditions for operating the secondary battery including the copper foil (10) and high temperature conditions for manufacturing an electrode from the copper foil (10).
[0113] The copper foil (10) above may have a welding index of 7 to 20 based on the first elongation rate according to Formula 3 below.
[0114] [Equation 3]
[0115] First elongation-based welding index (unit omitted) = (Welding strength / First elongation)
[0116] The copper foil (10) above may have a welding index of 6 to 18 based on the second elongation rate according to Formula 4 below.
[0117] [Equation 4]
[0118] Second elongation-based welding index (unit omitted) = (Welding strength above / Second elongation above)
[0119] The first elongation-based welding index may be an indicator representing the interfacial bonding quality and stress distribution efficiency of the copper foil (10) with the lead tab at room temperature. The second elongation-based welding index may be an indicator representing the interfacial stability and durability of the copper foil (10) with the lead tab at high temperature.
[0120] The above first elongation-based welding index may be 7 to 20, 7.6 to 20, 7.6 to 19, or 13 to 19.
[0121] The above second elongation standard welding index may be 6 to 18, 6.5 to 18, 6.5 to 17.5, or 14 to 17.5.
[0122] When the above range is satisfied, the welded portion of the copper foil (10) with the lead tab can be stably maintained in room temperature and high temperature environments, thereby ensuring mechanical stability of the electrode structure including the copper foil (10).
[0124] Figure 2 schematically shows a cross-sectional view of a cathode according to an embodiment.
[0125] The electrode according to the present invention may include a current collector comprising a copper foil (10) and an active material layer formed on at least one surface of the current collector.
[0126] The above electrode may be a negative electrode (100). The above active material layer may be a negative active material layer (15).
[0127] The copper foil (10) comprises a copper film (11) doped with at least one element among nitrogen and sulfur, and has a welding strength of 50 kgf / mm according to the following measurement method 1. 2 Up to 90 kgf / mm 2 It could be.
[0128] [Measurement Method 1]
[0129] 1) Prepare a copper film laminate in which 30 of the above copper films are stacked.
[0130] 2) The copper film laminate and the lead tab are welded according to the following laser welding conditions.
[0131] - Output: 2,500 W
[0132] - Impedance length: 39 mm
[0133] - Exposure interval: 1 mm
[0134] - Investigation time: 4 ms
[0135] 3) For the welded portion of the copper film laminate and the lead tab, the weld strength is measured using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min.
[0136] The copper foil (10) may include a protective film (12) formed on at least one surface of the copper film (11). The copper foil, copper film, protective film, and welding strength according to measurement method 1 may be the same as the copper foil, copper film, protective film, and welding strength according to measurement method 1 described above.
[0137] In FIG. 2 above, the protective film (12) and the negative active material layer (15) formed on one side of the copper film (11) are shown, but the protective film (12) and the negative active material layer (15) may be formed on both sides of the copper film (11).
[0138] The ratio of the thickness of the current collector may be 1% to 12%, 3% to 12%, 5% to 12%, or 6% to 12% relative to the total thickness of the electrode. When the above range is satisfied, the mechanical support of the negative electrode active material layer (15) can be maintained and the energy density can be improved.
[0139] The above negative electrode active material layer (15) may include a negative electrode active material.
[0140] The type of the above-mentioned negative electrode active material is not particularly limited, and compounds capable of reversible intercalation and deintercalation of lithium may be used. For example, carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, and highly crystalline carbon; and metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys, may be used. Examples of low-crystallinity carbon include soft carbon and hard carbon, while examples of highly crystalline carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes. The above-mentioned cathode active material may be a composite material including a metallic compound and a carbonaceous material, depending on the needs.
[0141] The above negative electrode active material can be mixed with a binder and a conductive material to form a negative electrode active material layer (15).
[0142] The bonding strength between the cathode active material and the conductive material can be improved by the above binder, and the bonding strength between the cathode active material layer (15) and the copper foil (10) can be improved.
[0143] The type of binder mentioned above is not particularly limited, but for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, styrene butadiene rubber (SBR), cellulose-based resin, etc. may be used.
[0144] The conductivity of the cathode active material can be improved by the above conductive material. The type of the above conductive material is not particularly limited, but, for example, Super-P, graphite, acetylene black, etc. may be used.
[0145] The electrode may include a primer layer disposed between the copper foil (10) and the negative active material layer (15).
[0146] The interfacial adhesion between the copper foil (10) and the negative active material layer (150) can be improved by the primer layer.
[0147] The primer layer may include a thickener. The thickener may include one or more selected from the group consisting of carboxymethyl cellulose (CMC), methyl cellulose (MC), hydroxypropyl cellulose (HPC), methyl hydroxypropyl cellulose (MHPC), ethyl hydroxyethyl cellulose (EHEC), methyl ethyl hydroxyethyl cellulose (MEHEC), and cellulose gum.
[0148] The primer layer may include a binder. The binder may include one or more selected from the group consisting of styrene butadiene rubber, polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, styrene monomer (SM), butadiene (BD), and butyl acrylate (BA).
[0149] The primer layer may include one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, metal fiber, fluorinated carbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives to improve conductivity.
[0151] Figure 3 schematically shows a cross-sectional view of a secondary battery according to an embodiment.
[0152] A secondary battery (1000) according to the present invention comprises a negative electrode (100), a positive electrode (200), an electrolyte (300), and a separator (400) interposed between the negative electrode (100) and the positive electrode (200); the negative electrode (100) comprises a current collector comprising a copper foil (10); the copper foil (10) comprises a copper film doped with at least one element among nitrogen and sulfur; and the welding strength according to the following measurement method 1 is 50 kgf / mm 2 Up to 90 kgf / mm 2 It could be.
[0153] [Measurement Method 1]
[0154] 1) Prepare a copper film laminate in which 30 of the above copper films are stacked.
[0155] 2) The copper film laminate and the lead tab are welded according to the following laser welding conditions.
[0156] - Output: 2,500 W
[0157] - Impedance length: 39 mm
[0158] - Exposure interval: 1 mm
[0159] - Investigation time: 4 ms
[0160] 3) For the welded portion of the copper film laminate and the lead tab, the weld strength is measured using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min.
[0161] The welding strength according to the above-described cathode (100) and measurement method 1 may be the same as the welding strength according to the above-described cathode and measurement method 1.
[0162] The above anode (200) may include a structure in which an anode active material layer (25) is formed on an anode current collector (20).
[0163] The anode (200) can be manufactured using general methods known in the field. For example, the anode (200) can be manufactured by mixing and stirring a solvent, binder, conductive material, and dispersant with an anode active material to prepare a slurry, then applying it to the anode current collector (20), compressing it, and drying it.
[0164] The positive current collector (20) is a highly conductive metal, and is a metal to which the slurry of the positive active material can easily adhere. It is not particularly limited as long as it has high conductivity without causing chemical changes in the secondary battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc., may be used. In addition, fine irregularities may be formed on the surface of the positive current collector to increase the adhesion of the positive active material. The positive current collector (20) may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., and may have a thickness of 3 μm to 500 μm.
[0165] The above-mentioned positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically, may include a lithium composite metal oxide comprising lithium and one or more metals such as cobalt, manganese, nickel, or aluminum.
[0166] The above electrolyte (300) may be a non-aqueous electrolyte. The above electrolyte (300) may include a lithium salt and an organic solvent. The above organic solvent may include at least one of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), methylpropyl carbonate (MPC), dipropyl carbonate (DPC), vinylene carbonate (VC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, sulfolane, gamma-butyrolactone, propylene sulfide, or tetrahydrofuran.
[0167] The separator (400) may be configured to prevent an electrical short circuit between the cathode (100) and the anode (200) and to allow for the flow of ions. The separator (400) may include a porous polymer film or a porous nonwoven fabric. Here, the porous polymer film may be composed of a single layer or multiple layers including polyolefin-based polymers such as ethylene polymer, propylene polymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer. The porous nonwoven fabric may include high-melting-point glass fibers or polyethylene terephthalate fibers. However, it is not limited thereto, and depending on the embodiment, the separator may be a high-heat-resistant separator (CCS; Ceramic Coated Separator) including ceramic.
[0168] The contact angle between the cathode (100) and the electrolyte (300) may be 50° or less, 45° or less, 40° or less, or 10° to 50° or less. The contact angle may be measured according to ASTM D7334. When the above range is satisfied, the surface wettability of the cathode (100) is excellent, so the uniformity of the SEI (Solid Electrolyte Interphase) layer can be improved, and the initial output characteristics and lifespan stability of the secondary battery (1000) can be improved.
[0170] Figure 4 schematically shows a copper foil manufacturing apparatus according to an embodiment.
[0171] A copper foil (10) according to the present invention can be manufactured by the above copper foil manufacturing device.
[0172] The method for manufacturing the copper foil (10) may include the step of forming a copper film (11) and the step of forming a protective film (12) on the copper film (11).
[0173] The manufacturing device for the copper foil (10) may include an electrolytic cell (30) for receiving an electrolyte (40), an anode plate (50) including a first anode plate (51) and a second anode plate (52), and a rotating cathode drum (60).
[0174] The first positive plate (51) and the second positive plate (52) may be electrically insulated.
[0175] The formation of the copper film (11) can be carried out by forming a seed layer through current flow between the first anode plate (51) and the rotating cathode drum (60), and growing the seed layer through current flow between the second anode plate (52) and the rotating cathode drum (60).
[0176] The current density provided by the first positive plate (51) and the second positive plate (52), respectively, may be 40 ASD to 130 ASD, 45 ASD to 130 ASD, 45 ASD to 125 ASD, or 45 ASD to 120 ASD. When the above range is satisfied, the formation of the negative active material layer (15) on the copper foil (10) can be smoothly performed, and sufficient adhesion between the copper foil (10) and the negative active material layer (15) can be provided.
[0177] The surface characteristics of the copper film (11) can be adjusted according to the degree of surface buffing or polishing of the rotating cathode drum (60). For example, the surface of the rotating cathode drum (60) can be polished with a polishing brush having a grit of #800 to #3000.
[0178] During the process of forming the copper film (11), the temperature of the electrolyte (40) may be maintained at 45°C to 65°C, 47°C to 65°C, 47°C to 63°C, or 47°C to 60°C. Depending on the temperature of the electrolyte (40), the size, crystal direction, and electrodeposition rate of the copper crystal grains may vary, and as a result, mechanical properties and surface roughness may be controlled.
[0179] The above electrolyte (40) may include copper ions, an inorganic acid, and an additive. The above electrolyte (40) may include chlorine. The above inorganic acid may include sulfuric acid.
[0180] The copper ion content in the above electrolyte (40) may be 70 g / L to 150 g / L, 70 g / L to 110 g / L, 70 g / L to 100 g / L, or 70 g / L to 90 g / L.
[0181] The copper ions contained in the above electrolyte (40) may be obtained by acid-washing a copper wire (Cu wire) with a purity of 99.9% or higher in 10% sulfuric acid for 10 to 20 minutes, followed by a washing process with distilled water. By the washing process, the acid-washed organic matter may be prevented from entering the above electrolyte (40). The concentration of the organic matter may be controlled by a filtration process using a medium such as diatomite or carbon.
[0182] The content of the sulfuric acid in the electrolyte (40) may be 80 to 130 g / L, 85 to 130 g / L, 90 to 130 g / L, or 90 to 125 g / L. Depending on the content of the sulfuric acid, the sulfur content doped in the copper film (11) may be controlled.
[0183] The chlorine may contain chloride ions and chloride atoms. The chlorine may be used to remove silver (Ag) ions introduced into the electrolyte (40) during the process of forming the copper film (11). The chlorine may precipitate the silver ions in the form of silver chloride (AgCl). The silver chloride may be removed by filtration.
[0184] The concentration of the chlorine may be 15 ppm to 30 ppm. When the above range is satisfied, the removal of the silver ions can be carried out smoothly, and unnecessary reactions caused by an excess amount of chlorine can be suppressed.
[0185] The above additive may include a first additive that can impart surface gloss, stress reduction, and flattening functions to the copper film (11).
[0186] The charge amount of the electrolyte (40) is increased by the first additive above, so that the electrodeposition rate of the copper ions can be increased, the curl characteristics of the copper foil (10) being manufactured can be improved, and the gloss of the copper foil (10) can be improved.
[0187] The concentration of the first additive may be 1 ppm to 20 ppm, 2 ppm to 20 ppm, 3 ppm to 20 ppm, or 3 ppm to 18 ppm. When the above range is satisfied, the surface roughness of the copper foil (10) being manufactured is maintained and the gloss can be improved. The sulfur content doped in the copper film (11) can be controlled according to the content of the first additive.
[0188] The first additive above may include sulfonic acid or its metal salt.
[0189] The first additive may include at least one of bis-(3-sulfopropyl)-disulfide disodium salt, diethylenetriaminepenta(methylenesulfonic acid), 3-mercapto-1-propanesulfonic acid, 3-(N,N-dimethylthiocarbamoyl)-thiopropanesulfonate sodium salt, 3-[(amino-iminomethyl)thio]-1-propanesulfonate sodium salt, o-ethyldithiocarbonato-S-(3-sulfopropyl)-ester sodium salt, 3-(benzothiazolyl-2-mercapto)-propyl-sulfonic acid sodium salt, and ethylenedithiodipropylsulfonic acid sodium salt.
[0190] The above additive may include a second additive that can provide a function to reduce the electrodeposition speed and improve the uniformity of the copper film (11).
[0191] The rapid increase in roughness and decrease in strength of the copper film (11) can be prevented by the second additive above.
[0192] The concentration of the second additive may be 0.1 ppm to 10 ppm, 0.2 ppm to 10 ppm, 0.3 ppm to 10 ppm, or 0.5 ppm to 10 ppm. When the above range is satisfied, wrinkles and tearing of the copper foil (10) being manufactured can be prevented, and physical properties such as appearance, gloss, strength, and elongation can be maintained.
[0193] The second additive mentioned above may include a nonionic water-soluble polymer.
[0194] The second additive above may include at least one of hydroxyethylenecellulose, hydroxypropylcellulose, ethylcellulose, carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, polyethylene glycol, polyvinyl alcohol, polypropylene glycol, polyacrylamide, polyoxyethylene, polyvinylpyrrolidone, polyethylene-polypropylene copolymer, polyglycerin, polyethylene glycol dimethyl ether, stearic acid polyglycol ether, and stearyl alcohol polyglycol ether.
[0195] The above additive may include a third additive that prevents electrodeposition blockage in the fine pattern of the copper film (11) and maintains flatness.
[0196] By suppressing electrodeposition in the region of the copper film (11) where the local current density is high due to the third additive, a leveling action can be performed to make the surface of the copper film (11) flat.
[0197] The concentration of the third additive may be 1 ppm to 10 ppm, 1 ppm to 9.5 ppm, or 1 ppm to 9 ppm. When the above range is satisfied, the surface gloss of the copper foil (10) being manufactured is uniform, and the phenomenon of a rapid increase in surface roughness can be suppressed. Depending on the content of the third additive, the sulfur content and / or nitrogen content doped in the copper film (11) can be controlled.
[0198] The above third additive may include at least one of thiourea, thiourea derivatives, diethylenethiourea, ethylenethiourea, polyethyleneimine, and 2-thiazolin-2-thiol.
[0199] The above additive may include a nitrogen-containing heterocyclic quaternary ammonium salt or a derivative thereof.
[0200] The above nitrogen-containing heterocyclic quaternary ammonium salt or its derivative may include at least one of the compounds represented by the following chemical formulas 1 to 5.
[0201] [Chemical Formula 1]
[0202]
[0203] [Chemical Formula 2]
[0204]
[0205] [Chemical Formula 3]
[0206]
[0207] [Chemical Formula 4]
[0208]
[0209] [Chemical Formula 5]
[0210]
[0211] In the above chemical formulas 1 to 5, ℓ1 to ℓ4, m1 to m4, and n1 to n5 each represent a repeating unit, are integers greater than or equal to 1, and may be identical or different from each other.
[0212] The number average molecular weight of each of the compounds represented by the above chemical formulas 1 to 5 may be 500 g / mol to 12,000 g / mol. When the above range is satisfied, the increase in surface roughness variation may be suppressed, and the glossiness and flatness of the copper film (11) may be improved.
[0213] The compounds represented by Chemical Formulas 1 to 5 above can be prepared by polymerization or copolymerization using DDAC (Diallyl dimethyl ammonium chloride). The compound represented by Chemical Formula 1 above may be PAS-2451 (Mw 30,000 g / mol, Nittobo). The compound represented by Chemical Formula 2 above may be PAS-84 (Mw 20,000 g / mol, Nittobo). The compound represented by Chemical Formula 3 above may be PAS-2351 (Mw 25,000 g / mol, Nittobo). The compound represented by Chemical Formula 4 above may be PAS-A-1 (Mw 5,000 g / mol, Nittobo) or PAS-A-5 (Mw 4,000 g / mol, Nittobo). It may be PAS-J-81 (Mw 180,000 g / mol, Nittobo), a compound represented by the above chemical formula 5.
[0214] The above additive may include a fourth additive for controlling the growth direction of the copper film (11) and for particle refinement.
[0215] Fine grains of the copper film (11) can be induced by the above-mentioned fourth additive, and surface flattening and thermal stability can be enhanced.
[0216] The concentration of the fourth additive may be 0.5 ppm to 20 ppm, 1 ppm to 20 ppm, 2 ppm to 20 ppm, or 3 ppm to 20 ppm. When the above range is satisfied, the thermal stability and surface flatness of the copper film (11) may be improved, and the tensile strength may be enhanced.
[0217] The above-mentioned fourth additive may include a protein derivative. The protein derivative may include at least one of collagen, collagen peptide, and gelatin.
[0218] The weight-average molecular weight of the protein derivative may be 1,000 g / mol to 10,000 g / mol, 1,000 g / mol to 10,000 g / mol, 1,000 g / mol to 10,000 g / mol, or 1,000 g / mol to 10,000 g / mol. When the above range is satisfied, the surface flattening of the copper film (11) can be improved, and the occurrence of bubbles and pores on the surface of the copper film (11) due to the increase in the viscosity of the electrolyte (40) can be suppressed.
[0219] The above protein derivative may include an α-helix structure and a β-sheet structure. The α-helix structure enables stable adsorption with copper ions due to strong hydrogen bonding, and the current distribution can be uniform depending on the layered structure. The β-sheet structure is an average structure that enables wide surface area coverage, forms a porous network, allows for selective ion permeability, and enables large crystallization.
[0220] The ratio of the above α-Helix structure to the above β-Sheet structure may be 7:3 to 3:7, 6.5:3.5 to 3:7, 6.5:3.5 to 3.5:6.5, or 6:4 to 4:6. When the above range is satisfied, side reactions with chloride ions can be suppressed, thereby improving current efficiency and preventing an increase in the rate of pore formation due to the accumulation of the β-Sheet structure.
[0221] The content of hydrogen peroxide (H2O2) in the above electrolyte (40) may be 1 ml / L to 10 ml / L, 1 ml / L to 9.5 ml / L, 1 ml / L to 9.2 ml / L, or 1 ml / L to 9 ml / L.
[0222] The concentration of silver (Ag) in the above electrolyte (40) may be 0.1 ppm to 10 ppm, 0.1 ppm to 9.5 ppm, 0.1 ppm to 9 ppm, or 0.1 ppm to 8 ppm.
[0223] The concentration of cerium (Ce) in the above electrolyte (40) may be 2 ppm to 10 ppm, 2 ppm to 9.5 ppm, 2 ppm to 9 ppm, or 2 ppm to 8 ppm.
[0224] The concentration of lead (Pb) in the electrolyte (40) may be 1 ppm to 20 ppm, 1 ppm to 19 ppm, 1 ppm to 18 ppm, or 1 ppm to 15 ppm.
[0225] The concentration of molybdenum (Mo) in the above electrolyte (40) may be 25 ppm or less, 20 ppm or less, 15 ppm or less, or 0.1 ppm to 25 ppm.
[0226] The concentration of nickel (Ni) in the above electrolyte (40) may be 15 ppm to 150 ppm, 15 ppm to 130 ppm, 15 ppm to 120 ppm, or 15 ppm to 100 ppm.
[0227] The concentration of tungsten (W) in the above electrolyte (40) may be 0.3 ppm to 5 ppm, 0.3 ppm to 4.5 ppm, 0.3 ppm to 4.2 ppm, or 0.3 ppm to 4 ppm.
[0228] The concentration of cobalt (Co) in the above electrolyte (40) may be 330 ppm or less, 320 ppm or less, 300 ppm or less, or 100 ppm to 330 ppm.
[0229] The concentration of iron (Fe) in the above electrolyte (40) may be 300 ppm or less, 280 ppm or less, 250 ppm or less, or 0.1 ppm to 300 ppm.
[0230] The concentration of arsenic (As) in the above electrolyte (40) may be 0.5 ppm to 5 ppm, 0.5 ppm to 4.5 ppm, 0.5 ppm to 4.2 ppm, or 0.5 ppm to 4 ppm.
[0231] The concentrations of the above silver, cerium, lead, molybdenum, nickel, tungsten, cobalt, iron, and arsenic include all atoms present in the ions and molecules.
[0232] When the above range is satisfied, the microstructure at the surface and interface of the copper foil (10) can be maintained uniformly through the active control of the crystal grains of the copper foil (10). Accordingly, stress concentration at the welding interface between the copper foil (10) and the lead tab can be suppressed, thereby preventing defects that may occur during welding and suppressing the deterioration of welding strength. As a result, the welding strength according to the aforementioned measurement method 1 is 50 kgf / mm 2 Up to 80 kgf / mm 2 It can satisfy.
[0233] When forming the copper film (11), the flow rate of the electrolyte (40) supplied into the electrolytic cell (30) is 35 m 3 / hour to 46 m 3 / hour, 37 m 3 / hour to 46 m 3 / hour, 39 m 3 / hour to 46 m 3 / hour, or 41 m 3 / hour to 45 m 3 It may be / hour. If the above range is satisfied, the electrolyte (40) is filtered during the circulation process of the electrolyte (40), and solid impurities present in the electrolyte (40) can be removed while electroplating for forming the copper film (11) is performed.
[0234] The flow rate deviation of the above electrolyte (40) can be controlled to 5% or less, 4% or less, 3% or less, or 2% or less per unit time (second). When the above range is satisfied, the copper film (11) can be formed uniformly, and the weight deviation of the manufactured copper foil (10) can be minimized.
[0235] In order to remove impurities from the surface of the copper film (11), water washing may be performed in the cleaning tank. In order to remove impurities from the surface of the copper film (11), after acid cleaning is performed, water cleaning may be performed to remove the acidic solution used in the acid cleaning.
[0236] The method for manufacturing the copper foil (10) may include the step of forming a protective film (12) on the copper film (11). The copper film (11) may be immersed in an anticorrosion solution (70). When the copper film (11) is immersed in the anticorrosion solution (70), it may be guided by a guide roll placed within the anticorrosion solution (70).
[0237] The above anti-corrosion liquid (70) may include at least one of a chromium compound, a silane compound, and a nitrogen compound. When forming the protective film (12) on the copper film (11), a method of immersing the copper film (11) in a potassium dichromate solution of 1 g / L to 10 g / L at room temperature for 1 second to 30 seconds may be implemented. The protective film (12) may include a silane compound by silane treatment and a nitrogen compound by nitrogen treatment. A copper foil (10) may be manufactured by forming the protective film (12).
[0239] The present invention will be described in more detail below based on examples and comparative examples. However, the following examples and comparative examples are merely illustrative for further explaining the present invention, and the present invention is not limited by the following examples and comparative examples.
[0241] Examples
[0242] Example 1
[0243] A copper foil was manufactured using a foil making machine comprising an electrolytic cell (30), a rotating cathode drum (60) disposed in the electrolytic cell (30), and an anode plate (50) disposed spaced apart from the rotating cathode drum (60).
[0244] The electrolyte (40) is a copper sulfate solution, the copper ion concentration in the electrolyte (40) is 87 g / L and the sulfuric acid concentration is 98 g / L, the temperature of the electrolyte (40) is 55 ℃ and the current density is 60 ASD (A / dm²). 2 It was set to ). In addition, the chlorine (Cl) concentration contained in the electrolyte (40) was maintained at 20 ppm.
[0245] The above electrolyte (40) contained 10 ppm of bis-(3-sulfopropyl)-disulfide disodium salt (SPS), 5 ppm of polyethylene glycol (PEG), 1 ppm of diethylene thiourea (DETU), and 1 ppm of polyethyleneimine (PEI).
[0246] A copper film (11) was manufactured by applying a current at a current density of 60 ASD between the rotating cathode drum (60) and the anode plate (50). Afterward, the copper film (11) was immersed in an anti-corrosion solution (70) for about 2 seconds. The anti-corrosion solution (70) had chromic acid as its main component, and the concentration of the chromic acid was 5 g / L.
[0247] Afterwards, a copper foil (10) with a thickness of 6 μm was manufactured by chromate treatment on both sides of the copper film (11) to form a protective film.
[0249] Examples 2 to 3 and Comparative Examples 1 to 3
[0250] Copper foil was manufactured under the same process conditions as Example 1, except that the main composition of the electrolyte and the content of each composition listed in Table 1 below were applied.
[0252] division Sulfuric acid (g / L) SPS(ppm) PEG(ppm) DETU(ppm) PEI(ppm) ETU 1) (ppm) TTZ 2) (ppm) Example 1 98 10 5 1 1 - - Example 2 95 10 5 - - 1 1 Example 3 87 10 5 1 - - 1 Comparative Example 1 95 10 5 0.1 - - - Comparative Example 2 92 2 5 - - 0.1 - Comparative Example 3 95 20 5 - 5 - 5 1) ETU: Ethylene thiourea2) TTZ: 2-Thiazoline-2-thiol
[0254] Experimental Example
[0255] Experimental Example 1 - Evaluation of Doping Elements
[0256] Samples of each copper foil prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were prepared. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) analysis was performed on each of the samples. The analysis involved quantitative evaluation of nitrogen and / or sulfur elements on the surface of the solid samples. The evaluation was performed according to the following criteria, and the results are shown in Table 2 below.
[0257] - Excess: The content of the above nitrogen and sulfur elements exceeds 80 ppm
[0258] - Titration: The content of the above nitrogen and sulfur elements is 20 ppm to 80 ppm
[0259] - Small amount: Content of the above nitrogen and sulfur elements is less than 20 ppm
[0261] Experimental Example 2 - Welding Strength
[0262] Each sample prepared in Experimental Example 1 above was prepared. After stacking 30 of the samples, ultrasonic welding was performed under the following conditions to produce a copper film laminate.
[0263] - Model: US-3620SLS
[0264] - Horn: Diamond knurling 1mm pitch
[0265] - Anivl: T200911YR-H-0.1
[0266] - Welding area: 45 mm x 6 mm
[0267] - Weld energy: 1,000 J
[0268] Subsequently, the copper film laminate and the lead tab were laser welded under the following conditions.
[0269] - Lead tab: Copper lead tab (45 mm x 43 mm)
[0270] - Model: AMB 4000
[0271] - Scanner: LWS-300
[0272] - Output: 2,500 W
[0273] - Impedance length: 39 mm
[0274] - Exposure interval: 1 mm
[0275] - Investigation time: 4 ms
[0276] Subsequently, regarding the copper film laminate and the lead tab weldment, a universal testing machine from Instron was used in accordance with the IPC-TM-650 standard to measure the weld strength under conditions of a length of 50 mm, a width of 12.7 mm, and a test speed of 50 mm / min. The results are shown in Table 2 below.
[0277] Separately, after stacking 50 of the above samples, the welding strength was measured using the same method and conditions as above, and the results are shown in Table 2 below.
[0279] Experimental Example 3 - Tensile Strength and Elongation
[0280] For each sample prepared in Experimental Example 1 above, a universal testing machine from Instron was used according to the IPC-TM-650 standard to measure the first tensile strength and first elongation at room temperature under conditions of a length of 50 mm, a width of 12.7 mm, and a test speed of 50 mm / min. Separately, after each sample was heat-treated at 190 ℃ for 10 minutes, the second tensile strength and second elongation were measured according to the same measurement method as above, and the results are shown in Table 2 below.
[0282] Experimental Example 4 - Welding Efficiency
[0283] For the welding strength, first tensile strength, and second tensile strength measured in Experimental Examples 2 and 3 above, the welding efficiency according to Equations 1 and 2 below was calculated, and the results are shown in Table 2 below.
[0284] [Equation 1]
[0285] First welding efficiency = (the above welding strength / the above first tensile strength) × 100
[0286] [Equation 2]
[0287] Second welding efficiency = (Above welding strength / Above second tensile strength) × 100
[0288] However, the welding strength in the above Equations 1 and 2 is based on 30 stacks.
[0290] Experimental Example 5 - Welding Index Based on Elongation
[0291] For the welding strength, first elongation, and second elongation measured in Experimental Examples 2 and 3 above, the elongation-based welding index according to Equations 3 and 4 below was calculated, and the results are shown in Table 2 below.
[0292] [Equation 3]
[0293] First elongation-based welding index (unit omitted) = (Welding strength / First elongation)
[0294] [Equation 4]
[0295] Second elongation-based welding index (unit omitted) = (Welding strength above / Second elongation above)
[0296] However, the welding strength in the above Equations 3 and 4 is based on 30 stacks.
[0298] Experimental Example 6 - Evaluation of Interfacial Defects After Welding
[0299] For each sample welded to the lead tab in Experimental Example 2 above, an optical microscope was used to observe the interface of the welded area. It was evaluated according to the following criteria, and the results are shown in Table 2 below.
[0300] - ◎: No cross-sectional discoloration or signs of oxidation, and a uniform interface is formed.
[0301] - △: No cross-sectional discoloration or traces of oxidation, but some parts of the interface are unevenly formed
[0302] - ×: Cross-sectional wall color and / or traces of oxidation confirmed
[0304] Experimental Example 7 - Evaluation of Fracture Occurrence
[0305] An active material slurry was applied to each copper foil prepared in Examples 1 to 3 and Comparative Examples 1 to 3. The active material slurry was prepared by mixing 2 parts by weight of styrene-butadiene rubber (SBR) and 2 parts by weight of carboxymethylcellulose (CMC) with respect to 100 parts by weight of graphite. The active material slurry was uniformly applied onto the copper foil using a roll-to-roll method and in the Machine Direction (MD) direction, and then dried. The application amount of the active material slurry was approximately 16 mg / cm². 2 The thickness was approximately 100 μm. After the active material slurry was dried, a roll press process was carried out under conditions of a roll gap of 6 μm, a speed of 1 m / min, a linear pressure of 1,000 kgf / cm, and a pressure of 2,500 kg, so that the density was approximately 1.5 g / cm³. 3A phosphorus active material layer was formed. Subsequently, a negative electrode with the lead tab welded onto the copper foil was manufactured by the same process as in Experimental Example 2. For each of the negative electrodes, a lithium manganese aluminum-based active material was used as the counter electrode (anode), a polypropylene sheet with a thickness of 0.1 mm was used as the separator, and a secondary battery was manufactured by using a solvent in which LiPF61M was dissolved in a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7 as the electrolyte.
[0306] Each of the above secondary batteries was charged with a constant current of 0.1C until the voltage reached 0.01V, and the process of discharging with a constant current of 0.1C until the voltage reached 1.5V was performed three times to stabilize the battery. Subsequently, each of the above secondary batteries was charged with a constant current of 0.5C until the voltage reached 0.01V, and the process of discharging with a constant current of 0.5C until the voltage reached 1.0V was performed 500 times. After 500 charge-discharge experiments were conducted, breakage between the copper foil and the lead tab was observed. It was evaluated according to the following criteria, and the results are shown in Table 2 below.
[0307] - Good: No lifting or breakage occurred between the copper foil and the lead tab.
[0308] - Defect: Lifting or breakage occurs between the copper foil and the lead tab
[0310] division Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Doping element evaluation titration titration titration handful handful plethora Welding strength (30 stack) 68.5 kgf / mm 2 69.5 kgf / mm 2 57.2 kgf / mm 2 45.6 kgf / mm 2 46.2 kgf / mm 2 82.5 kgf / mm 2 Welding strength (50 stack) 93.9 kgf / mm 2 89.8 kgf / mm 2 81.7 kgf / mm 2 73.6 kgf / mm 2 74.8 kgf / mm 2 110.5 kgf / mm 2 1st tensile strength 51 kgf / mm 2 64.1 kgf / mm 2 44.1 kgf / mm 2 42.5kgf / mm 2 53.6 kgf / mm 2 53.2 kgf / mm 2 Second tensile strength 49.9 kgf / mm 2 63 kgf / mm 2 38.7 kgf / mm 2 42.3 kgf / mm 2 53.3 kgf / mm 2 52.3 kgf / mm 2 First elongation 3.7 % 5.3 % 7.5 % 6.4 % 6.1 % 3.2 % Second elongation rate 4 % 4.9 % 8.8 % 7.6 % 6.8 % 3.5 % First welding efficiency 134.3 % 108.4 % 129.7 % 107.3 % 86.2 % 155.1 % Second welding efficiency 137.3 % 110.3 % 147.8 % 107.8 % 86.7 % 157.7 % First elongation-based welding index 18.5 13.1 7.6 7.1 7.6 25.8 Second elongation-based welding index 17.1 14.2 6.5 6.0 6.8 23.6 Assessment of interface defects after welding ◎ ◎ ◎ △ △ × Fracture occurrence assessment Good Good Good error error Good
[0312] According to Tables 1 and 2 above, the copper foil according to Examples 1 to 3 is doped with at least one element among nitrogen and sulfur, and the welding strength based on 30 stacks of the copper foil is 50 kgf / mm 2 Up to 80 kgf / mm 2 It meets the range. As a result, it was confirmed that the mechanical properties of the copper foil are stably maintained at room temperature and high temperature, no interfacial defects occur after welding, and the bonding reliability and durability of the weldment are improved. Explanation of the symbols
[0314] 10: Copper foil 11: Copper film 12: Shield 15: Cathode active material layer 20: Positive current collector 25: Positive active material layer 30: Electrolyzer 40: Electrolyte 50: Positive plate 51: First positive plate 52: Second positive plate 60: Rotating cathode drum 70: Anti-corrosion solution 100: Cathode 200: Anode 300: Electrolyte 400: Separator 1000: Secondary battery
Claims
Claim 1 It comprises a copper film doped with at least one element selected from nitrogen and sulfur, wherein the total content of the doping element is 20 ppm to 80 ppm, and the welding strength according to the following measurement method 1 is 50 kgf / mm 2 Up to 80 kgf / mm 2 Copper foil: [Measurement Method 1] 1) After stacking 30 copper films, prepare a copper film laminate by welding them according to the following ultrasonic welding conditions. - Horn: 1 mm pitch diamond knurling - Welding area: 45 mm x 6 mm - Weld energy: 1,000 J 2) Weld the copper film laminate and the lead tab according to the following laser welding conditions. - Output: 2,500 W - Irradiation length: 39 mm - Irradiation interval: 1 mm - Irradiation time: 4 ms 3) For the welded portion of the copper film laminate and the lead tab, measure the welding strength using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min. Claim 2 In claim 1, the welding strength according to the following measurement method 2 is 75 kgf / mm 2 Up to 100 kgf / mm 2 Copper foil: [Measurement Method 2] 1) After stacking 50 copper films, a copper film laminate is prepared by welding according to the ultrasonic welding conditions described in 1) of Measurement Method 1. 2) The welding strength is measured according to 2) and 3) of Measurement Method 1. Claim 3 delete Claim 4 In claim 1, the difference between the first tensile strength at room temperature according to the IPC-TM-650 and the second tensile strength after heat treatment at 190°C for 10 minutes is 6 kgf / mm 2 The above is as follows, and the first tensile strength is 40 kgf / mm 2 Up to 70 kgf / mm 2 Copper foil. Claim 5 In claim 4, a copper foil having a first welding efficiency of 100% to 140% according to the following Formula 1: [Formula 1] First welding efficiency = (The welding strength / The first tensile strength) × 100 Claim 6 In paragraph 4, a copper foil having a second welding efficiency of 110% to 160% according to the following Equation 2: [Equation 2] Second welding efficiency = (The welding strength / The second tensile strength) × 100 Claim 7 A copper foil according to claim 1, wherein the thickness of the copper foil is 6 μm ± 4 μm, the first elongation at room temperature according to the IPC-TM-650 is 2% to 15%, and the second elongation after heat treatment at 190 ℃ for 10 minutes is 3% to 20%. Claim 8 In claim 7, copper foil having a welding index based on a first elongation rate according to the following Equation 3, ranging from 7 to 20: [Equation 3] Welding index based on a first elongation rate (unit omitted) = (Welding strength / First elongation rate) Claim 9 In claim 7, copper foil having a welding index based on the second elongation rate according to the following Equation 4, ranging from 6 to 18: [Equation 4] Welding index based on the second elongation rate (unit omitted) = (Welding strength / Second elongation rate) Claim 10 The copper foil of claim 1, wherein the copper foil comprises a protective film formed on at least one surface of the copper film, and the protective film comprises at least one of a chromium compound, a silane compound, and a nitrogen compound. Claim 11 An electrode comprising a current collector including a copper foil; and an active material layer formed on at least one surface of the current collector, wherein the copper foil comprises a copper film doped with at least one element selected from nitrogen and sulfur, the total content of the doping element is 20 ppm to 80 ppm, and the welding strength according to the following measurement method 1 is 50 kgf / mm 2 Up to 80 kgf / mm 2 Electrode: [Measurement Method 1] 1) After stacking 30 copper films, prepare a copper film laminate by welding them according to the following ultrasonic welding conditions. - Horn: 1 mm pitch diamond knurling - Welding area: 45 mm x 6 mm - Weld energy: 1,000 J 2) Weld the copper film laminate and the lead tab according to the following laser welding conditions. - Output: 2,500 W - Irradiation length: 39 mm - Irradiation interval: 1 mm - Irradiation time: 4 ms 3) For the welded portion of the copper film laminate and the lead tab, measure the welding strength using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min. Claim 12 The apparatus comprises a cathode; an anode; an electrolyte; and a separator interposed between the cathode and the anode, wherein the cathode comprises a current collector comprising a copper foil, the copper foil comprises a copper film doped with at least one element selected from nitrogen and sulfur, the total content of the doping element is 20 ppm to 80 ppm, and the welding strength according to the following measurement method 1 is 50 kgf / mm 2 Up to 80 kgf / mm 2 Secondary battery: [Measurement Method 1] 1) After stacking 30 copper films, prepare a copper film laminate by welding them according to the following ultrasonic welding conditions. - Horn: 1 mm pitch diamond knurling - Welding area: 45 mm x 6 mm - Weld energy: 1,000 J 2) Weld the copper film laminate and the lead tab according to the following laser welding conditions. - Output: 2,500 W - Irradiation length: 39 mm - Irradiation interval: 1 mm - Irradiation time: 4 ms 3) For the welded portion of the copper film laminate and the lead tab, measure the welding strength using an Instron universal testing machine according to the IPC-TM-650 standard under conditions of length 50 mm, width 12.7 mm, and test speed 50 mm / min.
Citation Information
Patent Citations
Electrode for battery, and battery using it
JP2007214086A
Electrode assembly, cylindrical battery, and battery pack and vehicle including the same
KR1020220105142A
Copper foil capable of manufacturing high capacity secondary battery, electrode comprisng the same, secondary battery comprising the same and method for manufacturing the same
KR1020190025418A
JP05625141B1